Successful retrieval of lower limbs artery bone cement embolization resulting from percutaneous vertebroplasty: A rare case report - Jiashen Shao; Hai Feng; Bin Liu; Hai Meng; Shili Ning; Yingchi Yang; Yun Yang; Xuehu Xie; Zihan Fan; Zhiwu Zhang; Nan Su; Jinjun Li; et al. (Heliyon)
Percutaneous vertebroplasty (PVP) is a widely utilized minimally invasive technique originally developed for the treatment of vertebral compression fractures. It has since expanded to treat osteoporotic vertebral compression fractures, pathologic vertebral fractures resulting from primary or secondary spinal tumors, and traumatic spinal fractures. Despite its benefits, PVP is associated with significant complications, the most common of which is bone cement leakage. Arterial embolization due to cement leakage is a rare but increasingly recognized complication of PVP. Previous reports have documented cases of cement migrating into the aorta, renal arteries, and lower extremity arteries. However, with the growing use of PVP, the incidence of such vascular complications may rise. In this report, we present a rare case of bone cement leakage through the vertebral artery, leading to embolization in the inferior mesenteric artery and lower extremity arteries. The arterial embolus in the lower extremity was successfully treated with arteriotomy, highlighting the severe potential consequences of this complication and the importance of prompt recognition and intervention.